The Activation of JAK/STAT3 Signaling and the Complement System Modulate Inflammation in the Primary Human Dermal Fibroblasts of PXE Patients - Christopher Lindenkamp; Ricarda Plümers; Michel R. Osterhage; Olivier M. Vanakker; Judith Van Wynsberghe; Cornelius Knabbe; Doris Hendig (Biomedicines, 2023)
Previous studies revealed a link between inflammation and overactivation of the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling in syndromes associated with aging. Pseudoxanthoma elasticum (PXE), a rare autosomal-recessive disorder, arises from mutations in ATP-binding cassette subfamily C member 6 (ABCC6). On a molecular level, PXE shares similarities with Hutchinson–Gilford progeria syndrome, such as increased activity of senescence-associated- beta-galactosidase or high expression of inflammatory factors. Thus, this study’s aim was the evaluation of activated STAT3 and the influence of JAK1/2-inhibitor baricitinib (BA) on inflammatory processes such as the complement system in PXE. Analysis of activation of STAT3 was performed by immunofluorescence and Western blot, while inflammatory processes and complement system factors were determined based on mRNA expression and protein level. Our results assume overactivation of JAK/STAT3 signaling, increased expression levels of several complement factors and high C3 protein concentration in the sera of PXE patients. Supplementation with BA reduces JAK/STAT3 activation and partly reduces inflammation as well as the gene expression of complement factors belonging to the C1 complex and C3 convertase in PXE fibroblasts. Our results indicate a link between JAK/STAT3 signaling and complement activation contributing to the proinflammatory phenotype in PXE fibroblasts.